2023
DOI: 10.3389/fmed.2023.1037919
|View full text |Cite
|
Sign up to set email alerts
|

Precision (repeatability and reproducibility) of papillary and peripapillary vascular density measurements using optical coherence tomography angiography in children

Abstract: ImportanceOptical coherence tomography angiography (OCTA) has been widely applied into children, however, few studies have assessed the repeatability and reproducibility of papillary and peripapillary VD in healthy children.ObjectiveTo assess the precision of papillary and peripapillary vascular density (VD) measurements using optical coherence tomography angiography (OCTA) and analyze the effects of the signal strength index (SSI) and axial length (AL) on precision estimates.Design, setting, and participantsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The study of optic nerve head (ONH) perfusion has been recently popularized after progression in understanding glaucoma and ONH disease pathogeneses. It has been revealed that optic nerve circulation and anatomy may be altered by ocular diseases like high myopia 2 , infantile nystagmus 3 , optic disc drusen 4 , uveitis 5 , optic neuritis 6 , optic neuropathies 7 , glaucoma 8 , 9 , central nervus system (CNS) related disorders such as migraine 10 , epilepsy 11 , CNS tumors 12 , 13 , and systemic conditions like diabetes 14 and thalassemia 15 or drug induced changes 11 , 16 in both children and adults 12 , 17 , 18 . Prompt diagnosis and management are crucial to prevent further visual impairment and promote optimal visual development.…”
Section: Introductionmentioning
confidence: 99%
“…The study of optic nerve head (ONH) perfusion has been recently popularized after progression in understanding glaucoma and ONH disease pathogeneses. It has been revealed that optic nerve circulation and anatomy may be altered by ocular diseases like high myopia 2 , infantile nystagmus 3 , optic disc drusen 4 , uveitis 5 , optic neuritis 6 , optic neuropathies 7 , glaucoma 8 , 9 , central nervus system (CNS) related disorders such as migraine 10 , epilepsy 11 , CNS tumors 12 , 13 , and systemic conditions like diabetes 14 and thalassemia 15 or drug induced changes 11 , 16 in both children and adults 12 , 17 , 18 . Prompt diagnosis and management are crucial to prevent further visual impairment and promote optimal visual development.…”
Section: Introductionmentioning
confidence: 99%